Big and Little First Skills with Ladybird - Lesley Clark (Italy Ladybird Books Ltd., 2006)
This is a very useful first learning book to help children understand opposites like big, little, long and short. Children can have fun pointing to the pictures and saying the words, while finding out about the world around them.